Ionic liquid microwave-assisted extraction of annona muricata fruit - Daddiouaissa, Djabir; Amid, Azura; Kabbashi, Nassereldeen Ahmed; Mohd Shaifudin Epandy, Mohamad Adika Khairy (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Extraction method plays an essential role in extracting bioactive compounds. Ionic liquid microwave-assisted extraction (ILMAE) method has been successfully applied to get the optimum extraction yield from Annona muricata fruit. A series of the 1-butyl-3-methylimidazolium cation with different anions Cl-, BF4-, PF6- were assessed for extraction efficiency, and 1-butyl-3-methylimidazolium chloride was selected as the optimal solvent. Also, the microwave-assisted extraction parameters, including extraction time, power and solid-liquid ratio had been investigated. The response surface methodology was applied by using the extraction yield as response value to identify the optimum extraction condition. The optimum extraction condition is extraction time of 2 min, power of 300 W and a solid-liquid ratio of 1:25 g/mL. The extraction yield was 67.64% which is in close agreement with the value predicted by the model. Finally, ionic liquids as a green and designer solvents combined with microwave-assisted extraction could provide high extraction yields in less extraction time.